2018
DOI: 10.1002/cncy.22053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of peripheral lung adenocarcinoma in brush cytology obtained by EBUS plus fluoroscopy‐guided bronchoscopy

Abstract: BACKGROUND: More than 60% of patients with lung cancer are diagnosesd at advanced stages. The introduction of targeted therapies requires molecular diagnosis to guide treatment. The aim of this study was to evaluate the feasibility of performing mutational analysis with brushing specimens obtained by radial-miniprobe endobronchial ultrasound (R-EBUS) plus fluoroscopy-guided bronchoscopy in patients with peripheral pulmonary adenocarcinoma. METHODS:Brushing specimens were deposited on cytological slides and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…The mutations observed in the tumor in the present study do not differ substantially from those previously described for Caucasian patients exposed to tobacco smoking [19,26,27,28]. However, these genetic changes were present both in the tumor and the NTL parenchyma.…”
Section: Discussionsupporting
confidence: 50%
“…The mutations observed in the tumor in the present study do not differ substantially from those previously described for Caucasian patients exposed to tobacco smoking [19,26,27,28]. However, these genetic changes were present both in the tumor and the NTL parenchyma.…”
Section: Discussionsupporting
confidence: 50%
“…However, even when the sampling is not cytological but histological (e.g., endobronchial forceps biopsy, core needle biopsy) the agile cytopathologist can employ quick cytological techniques for rapid on-site evaluation and specimen triage [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Small biopsies can be used to prepare the whole array of cytological specimens in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our cases include a higher number with known mutations. We believe this is due to a lower number of cases tested in our cohort, since other studies on peripheral lung adenocar-cinomas have found that the molecular profile of those tumors is similar to that seen in the Western population [47,48]. Moreover, TT-NA was a preferred procedure in 15 cases to obtain tumor tissue for further molecular studies or evolution of tumor response to treatment.…”
Section: Discussionmentioning
confidence: 91%